(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
D. Annulatum F. and P. Distichum L., are grasses belongs to Poaceae family, they grow without any effort in the western plateau of Iraq in general and particulary in the southern part, located in the province of Muthanna. These grasses are commonly used as a forage for livestock. The present study was designed to evaluate the cytotoxic effect of D. Annulatum F. and P. Distichum L. methanolic extracts in vitro by using MTT assay (3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide) on two cell lines (SR and L20B) by using different concentrations (3.125, 6.25, 12.5, 25, 50, 100 and 200 μg/ml) for an incubation period of 24 hours. We found cytotoxic effect for methanolic extract of D. Annulatum F. against SR cell line in low concentrations (3.125, 6.25μg/ml) which was (55%, 46%), and against the L20B cell line was (60%, 59%) in the same concentrations. Regarding methanolic extract of P. Distichum L. the best effect was found with the lower concentrations which was (45%,44%) against SR and (49%,48%) against L20B. In conclusion, the two grasses have a good potential anticancer effects